Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How can I prove that $$\int_0^af(x) \; dx=\int_0^a f(a-x) \; dx$$

share|improve this question
add comment

2 Answers 2

up vote 5 down vote accepted

It's pedagogically better to give hints:

  1. Change of variables: If $a-x = u$ then $f(a-x) = f(u)$

  2. Change of variables: If $a-x = u$ then $dx = -du$

  3. Change of variables: If $a-x = u$ then $x =0 \iff u =\ \color{red}{??}$ and $x=a \iff u =\ \color{red}{??}$

  4. Interchange of boundary: $ \displaystyle\int_a^{b} f(x) dx = - \displaystyle\int_{b}^{a} f(x) dx$

  5. Formal variable renaming: $ \displaystyle\int_a^{b} f(x) dx = \displaystyle\int_{a}^{b} f(z) dz$

Can you fill in the $\color{red}{??}$ and put it all together?

share|improve this answer
    
Hhhh great thanks –  Rawhi Mar 17 '12 at 22:28
add comment

Use change of variables $u=a-x$

share|improve this answer
    
Apply this change to the integral on the right. You'll see that the change brought by the limits of integration and changing from dx to -du cancel out giving you the integral on the left with u instead of x. –  Steven-Owen Mar 17 '12 at 22:11
    
@Rawhi: Seriously, I guess that this problem can appear only after change of variables was taught, and it is maybe the most basic change of variables. –  Beni Bogosel Mar 17 '12 at 22:29
    
@Rawhi: I was surprised that you asked 'How this could help!!?', that's all. –  Beni Bogosel Mar 17 '12 at 22:44
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.